Dynamic monitoring of the historic centre buildings for a solar elements arrangement (using the example of Chernivtsi) - Шулдан, Лариса; Аль-Ахммаді, С. А.; Shuldan, Larysa; Al-Ahmmadi, S. A. (Lviv Politechnic Publishing House, 2017)
У статті розглянуто можливості інтеграції елементів сонячної енергетики в сформоване середовище історичних міст. На прикладі історичного ареалу міста Чернівці здійснено багаторівневий динамічний моніторинг будівель, подано результати попередніх розрахунків енергетичної ефективності встановлення фотоелектричних елементів на дахах.

The possibilities of integrating the solar power elements into formed environment of historic cities are considered in the article. Using the example of a historic city area of Chernivtsi it has been realized a multilevel dynamic monitoring of the buildings and presented the results of preliminary calculations of an energy efficiency of a roof photoelectric elements installation.
Динамічний моніторинг будівель історичного центру для розміщення солярних елементів (на прикладі міста Чернівці)
Keywords: енергоефективність; енергозбереження; енергетична модернізація; реконструкція; історична забудова; пам’ятка архітектури; моніторинг; сонячна енергія; фотовольтаіка; фотоелектричні елементи; energy (power) efficiency; energy saving; power (energy) updating; reconstruction; historic building; historic monument; monitoring; solar power; photo-voltage; photoelectric elements